Achieving Low Lattice Thermal Conductivity in Half‐Heusler Compound LiCdSb via Zintl Chemistry. Issue 12 (26th October 2022) - Yang, Xinxin; Yuan, Song; Guo, Kai; Ni, Heng; Song, Tao; Lyu, Wanyu; Wang, Da; Li, Han; Pan, Shusheng; Zhang, Jiye; Zhao, Jing-Tai
Abstract : Half‐Heusler compounds usually possess ultrahigh power factors, while the large thermal conductivity hinders the further optimization of their thermoelectric properties. Herein, from the perspective of material design, a new half‐Heusler lattice with low lattice thermal conductivity by using Zintl chemistry based on the composition of LiCdSb is rationally constructed. The weak bonding within the polyanions combined with the resonance vibration modes of Li + contributes to the small lattice thermal conductivity of pristine LiCdSb as low as 3.2 W m −1 K −1 at 303 K and 0.85 W m −1 K −1 at 573 K. Ag doping is further conducted for boosting the electronic quality factor B E from 2.5 to 5.2 μW cm −1 K −2 due to the energy band modulation. As a result, a high power factor up to 21.35 μW cm −1 K −2 at 393 K is achieved in LiCd0.94 Ag0.06 Sb. In view of the low thermal conductivity, the figure of merit zT reaches 0.79 at 633 K. Herein, it is demonstrated that the half‐Heusler compound LiCdSb is a competitive thermoelectric parent, and low thermal conductivity can indeed be realized in half‐Heusler compounds through Zintl chemistry. Abstract : A promising thermoelectric compound with a half‐Heusler lattice, LiCdSb, is constructed using Zintl chemistry, in which zinc blende (CdSb4/4 ) − tetrahedrons are treated as Zintl polyanions and Li + ions act as Zintl cations. The high‐symmetry, weak covalent bonding within the polyanionic framework, and weakly bound Li + lead to promising electrical and thermal transport properties.